PERANANAN AUDIT OPERASIONAL DALAM MENINGKATKAN JASA PELAYANAN PADA PT KAI PERSERO - Sari, Perwita Mustika (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The purpose of this research is to find out the role of operational audit in improving services. The relation between operational audit and service activity is an approach which is carried out to investigate, to evaluate, to detect and to study methods, procedures, policies, and service management activities. Afterward, the recommendation of improvement can be performed so the goal of operational audit to the service activity can be achieved. Therefore, the primary focus of service company is satisfaction to the customer. How far the performance which has been given by a product or service is equal to customerâs expectation.The result of research shows that: (1) it can be concluded from the calculation of Community Satisfaction Index which has been performed that the service of PT Kereta Api DAOP VIII Surabaya has been satisfactory, (2) the officer has been trying to give proper services, (3) the PT Kereta Api DAOP VIII Surabaya ticket reservation service has broaden their cooperation by performing online ticket selling which gives simplicity to the people in reserving tickets, (4) overall, the online selling system has make the customers easier to make reservation on the station, authorized agency and etc whenever and wherever.Keywords: Operational Audit, Service